Predictors of suicide in patients with conversion disorder - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2014)
Objective: Previous studies have shown that the ratio of suicide attempts is between 19.6 and 34.2% in patients with conversion disorder (CD), yet few studies have addressed this issue. The present study compared demographic and clinical variables and predictors of suicide attempts in patients with CD. Methods: A total of 100 consecutive patients were recruited and divided into groups according to their history of suicide attempts. Socio-demographic variables such as economic status, age, gender, educational level, marital status, clinical variables such as the presence of psychiatric disorder in family, substance abuse, risky alcohol use, age of onset, subtype of CD, number of hospitalization were recorded. Participants also completed the Childhood Trauma Questionnaire (CTQ-28), Temperament and Character Inventory (TCI), Toronto Alexithymia Scale (TAS-20), Dissociative Experiences Scale (DES), Beck Anxiety Inventory (BAT), and Beck Depression Inventory (BDI). Results: Suicide attempters had a higher rate of risky alcohol use, more hospitalizations, and higher mean scores on the BAI, BDI, DES/DES-taxon, TAS-total and CTQ-total than did non-suicide attempters or healthy control (NBC). Patients with CD had a higher harm-avoidance and a lower self-directedness rather than NBC. Risky alcohol use, number of hospitalizations, and mean DES-taxon and emotional abuse scores were independent predictors of suicide attempts. Conclusion: Our findings indicate that clinicians should be aware of the prediction of suicide in patients with CD who show dissociation and risky alcohol use. Moreover, a history of childhood emotional abuse should be considered in the management of CD. The fact that clinical variables distinguished between suicide attempters and non-attempters suggests that a history of suicide attempts may be used to clarify the heterogeneous nature of CD. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: TORONTO-ALEXITHYMIA-SCALE; CHILDHOOD TRAUMA; DISSOCIATIVE DISORDERS; TURKISH VERSION; SOMATIZATION; SYMPTOMS; WOMEN; RELIABILITY; TEMPERAMENT; VALIDATION